Hydrolysis-resistant high-barrier biodegradable film and preparation method thereof
A hydrolysis-resistant high-barrier biodegradable film is developed via esterification and polycondensation, using a thiophene ring and carbodiimide to enhance gas barrier and hydrolysis resistance, addressing the limitations of conventional degradable polyester materials.
Patent Information
- Application Number
- CN202411303804.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-27
AI Technical Summary
Conventional degradable polyester materials suffer from poor hydrolysis resistance and gas barrier properties, particularly in high-temperature and humid environments, limiting their long-term usability and functionality in packaging applications.
A hydrolysis-resistant high-barrier biodegradable film is produced through esterification and polycondensation of aromatic dibasic acid, aliphatic dibasic acid, aliphatic diol, 2-ethyl-2-butyl-propylene glycol, and polymeric carbodiimide, incorporating a thiophene ring in the molecular chain to enhance gas barrier performance and using carbodiimide to stabilize ester bonds against hydrolysis.
The film exhibits improved hydrolysis resistance and gas barrier properties, maintaining structural integrity and functionality under adverse conditions, with the thiophene ring and carbodiimide group effectively reducing gas permeation and stabilizing ester bonds.
Smart Images

Figure BDA0005048498900000061 
Figure BDA0005048498900000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of biodegradable polyester materials, and more specifically, to a hydrolysis-resistant and high-barrier biodegradable film and a preparation method thereof. Background Art
[0002] As people pay more and more attention to environmental pollution, people's requirements for polymer materials are not only excellent performance, but also relatively environmentally friendly. At the same time, in recent years, many policies encouraging the production of biodegradable materials have been introduced at home and abroad. Therefore, degradable materials such as PGA, PLA, PBS, PHA, PBAT, etc. have come into being.
[0003] Degradable polyester materials have good physical properties and are therefore widely used in film packaging and other fields. They can also be degraded into water and carbon dioxide under composting or natural conditions, and are basically harmless to the environment. However, most of these materials are composed of aliphatic polyesters or aliphatic / aromatic copolyesters, which have poor hydrolysis resistance in high temperature and humid environments. Therefore, these materials are easily damaged after long-term storage. At the same time, since packaging materials have certain requirements for gas barrier properties, when degradable polyester materials are used as packaging films, they are also required to have certain gas barrier properties.
[0004] Therefore, there is an urgent need for a hydrolysis-resistant, high-barrier biodegradable film to meet market demand. Summary of the invention
[0005] In order to improve the defects of relatively poor hydrolysis resistance and gas barrier properties of conventional degradable polyester materials, the present application provides a hydrolysis-resistant and high-barrier biodegradable film and a preparation method thereof.
[0006] In the first aspect, the present application provides a hydrolysis-resistant high-barrier biodegradable film, which adopts the following technical solution:
[0007] A hydrolysis-resistant high-barrier biodegradable film is obtained by esterification and polycondensation of aromatic dibasic acid, aliphatic dibasic acid, aliphatic diol, 2-ethyl-2-butyl-propylene glycol and polymeric carbodiimide, wherein the molecular chain of the aromatic dibasic acid contains a thiophene ring.
[0008] Since the vacancy steric hindrance of the side chain group in the 2-ethyl-2-butyl-propylene glycol monomer reduces the gas permeation, the gas barrier effect of the hydrolysis-resistant high-barrier biodegradable film is significantly improved. At the same time, since the aromatic dibasic acid contains a thiophene ring in the molecular chain, it is more difficult to flip it, and its hydrophilicity is poor, so the gas barrier performance and hydrolysis resistance of the hydrolysis-resistant high-barrier biodegradable film are significantly improved.
[0009] In addition, the reason that affects polyester hydrolysis is that water molecules attack the ester bonds in the polyester molecules, causing the polymer chain to break, and the terminal carboxyl group can accelerate the hydrolysis stability of the ester bond. Therefore, controlling the concentration of the terminal carboxyl group is one of the main means to improve polyester hydrolysis, and the carbodiimide group of the polymeric carbodiimide can react with the carboxyl group produced by hydrolysis, thereby effectively slowing down the continued occurrence of hydrolysis.
[0010] Preferably, the aromatic dibasic acid is one of 2,5-thiophenedicarboxylic acid and 2,5-thiophenedicarboxylic acid esters.
[0011] Preferably, the aromatic dibasic acid is a 2,5-thiophene dicarboxylic acid ester, and the 2,5-thiophene dicarboxylic acid ester is one of dimethyl 2,5-thiophene dicarboxylate, diethyl 2,5-thiophene dicarboxylate, dipropyl 2,5-thiophene dicarboxylate and dibutyl 2,5-thiophene dicarboxylate.
[0012] The aromatic dibasic acid can be 2,5-thiophenedicarboxylic acid or 2,5-thiophenedicarboxylic acid esters. However, compared with 2,5-thiophenedicarboxylic acid, 2,5-thiophenedicarboxylic acid esters have no acid group, thereby effectively reducing the acid value and improving the hydrolysis resistance of the hydrolysis-resistant high-barrier biodegradable film to a certain extent.
[0013] Preferably, the aliphatic dibasic acid is one of oxalic acid, succinic acid, adipic acid, glutaric acid, 1,1-cyclohexanedicarboxylic acid, itaconic acid and maleic acid.
[0014] Preferably, the aliphatic diol is one of 1,2-ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, 1,4-cyclohexanediol and isosorbide.
[0015] Preferably, the polymeric carbodiimide is made from the following raw materials: toluene diisocyanate-80, methanol and 3-methyl-1-phenyl-2-phospholene-1-oxide.
[0016] Preferably, the preparation method of the polymeric carbodiimide is:
[0017] First, under nitrogen, methanol is slowly added dropwise to toluene diisocyanate-80 for end-capping. The addition time is 0.5-1.5h, and the amount of methanol added is 30% of the amount of toluene diisocyanate-80.
[0018] After the methanol is added dropwise, add 0.01-0.02% of the total amount of toluene diisocyanate-80 as a catalyst 3-methyl-1-phenyl-2-phospholene-1-oxide, raise the temperature to 100-140°C, and react for 2-4h;
[0019] After the reaction is complete, the mixture is taken out and cooled to harden, then heated to 120-160°C and vacuum dried, and finally naturally cooled, fixed and crushed to obtain polymeric carbodiimide.
[0020] Preferably, the molar ratio of the aromatic dibasic acid, aliphatic dibasic acid, aliphatic diol, 2-ethyl-2-butyl-propylene glycol and polymeric carbodiimide is (0.45-0.5): (0.5-0.55): (0.6-1.6): (0.06-0.16): (0.1-0.2): (0.01-0.03).
[0021] When the aromatic dibasic acid, aliphatic dibasic acid, aliphatic diol, 2-ethyl-2-butyl-propylene glycol and polymeric carbodiimide are in the above molar ratio, the prepared hydrolysis-resistant high-barrier biodegradable film will have both better hydrolysis resistance and gas barrier effect.
[0022] In a second aspect, the present application provides a method for preparing a hydrolysis-resistant high-barrier biodegradable film, using the following technical solution:
[0023] A method for preparing a hydrolysis-resistant high-barrier biodegradable film comprises the following steps:
[0024] S1. First, aliphatic diol, 2-ethyl-2-butyl-propylene glycol, aliphatic dibasic acid, aromatic dibasic acid and n-butyl titanate are mixed and subjected to esterification reaction at a temperature of 160-220° C. The amount of n-butyl titanate added is 10% of the amount of aliphatic diol added. The reaction is carried out for 2-3 hours to obtain an esterified product.
[0025] S2. The esterification product is subjected to vacuum polycondensation reaction at a temperature of 220-240°C for a reaction time of 0.5-1.5h, and then 5% of the total mass of n-butyl titanate is added, and the vacuum polycondensation reaction is continued at 230-250°C for a reaction time of 2-4h, and then polymeric carbodiimide is added. After mixing evenly, extrusion cooling and stretching are performed to obtain a hydrolysis-resistant, high-barrier, biodegradable film with a thickness of 0.05-0.15mm.
[0026] In summary, this application has the following beneficial effects:
[0027] 1. The vacancy steric hindrance of the side chain group in the 2-ethyl-2-butyl-propylene glycol monomer reduces the gas permeation effect, which significantly improves the gas barrier effect of the hydrolysis-resistant high-barrier biodegradable film. At the same time, since the aromatic dibasic acid contains a thiophene ring in the molecular chain, it is more difficult to flip it, and its hydrophilicity is poor, so the gas barrier performance and hydrolysis resistance of the hydrolysis-resistant high-barrier biodegradable film are significantly improved.
[0028] 2. The reason that affects polyester hydrolysis is that water molecules attack the ester bonds in the polyester molecules, causing the polymer chain to break, and the terminal carboxyl group can accelerate the hydrolysis stability of the ester bond. Therefore, controlling the concentration of the terminal carboxyl group is one of the main means to improve polyester hydrolysis, and the carbodiimide group of the polymeric carbodiimide can react with the carboxyl group produced by hydrolysis, thereby effectively slowing down the continued occurrence of hydrolysis.
[0029] 3. The aromatic dibasic acid can be 2,5-thiophenedicarboxylic acid or 2,5-thiophenedicarboxylic acid ester. However, compared with 2,5-thiophenedicarboxylic acid, 2,5-thiophenedicarboxylic acid ester has no acid group, which effectively reduces the acid value and improves the hydrolysis resistance of the hydrolysis-resistant high-barrier biodegradable film to a certain extent.
[0030] 4. When the aromatic dibasic acid, aliphatic dibasic acid, aliphatic diol, 2-ethyl-2-butyl-propylene glycol and polymeric carbodiimide are used in a molar ratio of (0.45-0.5): (0.5-0.55): (0.6-1.6): (0.06-0.16): (0.1-0.2): (0.01-0.03), the prepared hydrolysis-resistant high-barrier biodegradable film will have both better hydrolysis resistance and gas barrier effect. DETAILED DESCRIPTION
[0031] The present application is further described in detail below in conjunction with Examples 1-4 and Comparative Examples 1-4.
[0032] raw material
[0033] 2,5-Thiophenedicarboxylic acid CAS: 4282-31-9; 2,5-Thiophenedicarboxylic acid dimethyl ester CAS: 4282-34-2; Succinic acid CAS: 110-15-6; 1,4-Butanediol CAS: 110-63-4; Toluene diisocyanate-80 Covestro Polymers (China) Co., Ltd. TDI-80; Methanol CAS: 67-56-1; 3-Methyl-1-phenyl-2-phosphocyclopentene-1-oxide TCI (Shanghai) Chemical Industry Development Co., Ltd.; 2-Ethyl-2-butyl-propylene glycol CAS: 115-84-4; n-Butyl titanate CAS: 5593-70-4; Dimethyl terephthalate CAS: 126-61-6; Thiodiglycol CAS: 111-48-8.
[0034] Example
[0035] Example 1
[0036] A hydrolysis-resistant high-barrier biodegradable film is obtained by esterification and polycondensation of aromatic dibasic acid, aliphatic dibasic acid, aliphatic diol, 2-ethyl-2-butyl-propylene glycol and polymeric carbodiimide.
[0037] The molar ratio of aromatic dibasic acid, aliphatic dibasic acid, aliphatic diol, 2-ethyl-2-butyl-propylene glycol and polymeric carbodiimide is 0.48:0.52:1.1:0.15:0.02, the aromatic dibasic acid is 2,5-thiophenedicarboxylic acid, the aliphatic dibasic acid is succinic acid, and the aliphatic diol is 1,4-butanediol.
[0038] The polymeric carbodiimide is prepared from the following raw materials: toluene diisocyanate-80, methanol and 3-methyl-1-phenyl-2-phosphopentene-1-oxide.
[0039] The preparation method of polymeric carbodiimide is:
[0040] First, under nitrogen, methanol was slowly added dropwise to toluene diisocyanate-80 for end-capping. The addition time was 1 hour, and the amount of methanol added was 30% of the amount of toluene diisocyanate-80.
[0041] After the methanol was added dropwise, 0.015% of the total amount of toluene diisocyanate-80 catalyst 3-methyl-1-phenyl-2-phospholene-1-oxide was added, the temperature was raised to 120°C, and the reaction was carried out for 3 hours;
[0042] After the reaction is complete, the mixture is taken out and cooled to harden, then heated to 140°C and vacuum dried, and finally naturally cooled, fixed and crushed to obtain polymeric carbodiimide.
[0043] The method for preparing a hydrolysis-resistant high-barrier biodegradable film comprises the following steps:
[0044] S1. First, aliphatic diol, 2-ethyl-2-butyl-propylene glycol, aliphatic dibasic acid, aromatic dibasic acid and n-butyl titanate are mixed and subjected to esterification reaction. The esterification temperature is 190° C., the amount of n-butyl titanate added is 10% of the amount of aliphatic diol added, and the reaction is performed for 2.5 hours to obtain an esterification product.
[0045] S2. The esterification product is subjected to vacuum polycondensation reaction at a temperature of 230°C for a reaction time of 1 hour, and then 5% of the total mass of n-butyl titanate is added, and the vacuum polycondensation reaction is continued at 240°C for a reaction time of 3 hours, and then polymeric carbodiimide is added. After mixing evenly, extrusion cooling and stretching are performed to obtain a hydrolysis-resistant, high-barrier, biodegradable film with a thickness of 0.1 mm.
[0046] Example 2-3
[0047] The difference from Example 1 is that the molar ratios of the aromatic dibasic acid, the aliphatic dibasic acid, the aliphatic diol, 2-ethyl-2-butyl-propylene glycol and the polymeric carbodiimide are different, as shown in Table 1.
[0048] Table 1 Molar ratio of each component of hydrolysis-resistant high barrier biodegradable film
[0049]
[0050]
[0051] Example 4
[0052] The difference from Example 1 is that 2,5-thiophenedicarboxylic acid is replaced by the same molar amount of dimethyl 2,5-thiophenedicarboxylate.
[0053] Comparative Example
[0054] Comparative Example 1
[0055] The difference from Example 1 is that no polymeric carbodiimide is added.
[0056] Comparative Example 2
[0057] The difference from Example 1 is that 2,5-thiophenedicarboxylic acid is replaced by the same molar amount of dimethyl terephthalate.
[0058] Comparative Example 3
[0059] The difference from Example 1 is that 0.3 mol of thiodiglycol is further added to S1.
[0060] Comparative Example 4
[0061] The difference from Example 2 is that no 2-ethyl-2-butyl-propylene glycol is added.
[0062] Performance testing
[0063] Detection Methods
[0064] 1. Hydrolysis resistance test
[0065] Three samples were taken out from Examples 1-4 and Comparative Examples 1-4, respectively, with a sample size of 2cm×2cm, and then placed in a constant temperature water bath at 95°C for a boiling test. Samples were taken after 72 hours, and the samples were wiped dry with gauze and placed in an oven at 80°C for 4 hours. After drying, the melt mass flow rate (MFR) was tested with a melt indexer and the average value was taken. The temperature was 190°C and the pressure was 2.16kg.
[0066] 2. Gas barrier test
[0067] Three samples were taken from Examples 1-4 and Comparative Examples 1-4 respectively, with the sample size of 10 cm×10 cm×0.2 mm. The oxygen permeability coefficients of the samples were tested using a BSG-33E gas permeability tester and the average value was taken. The test conditions were: 1 atm, 23° C., and an oxygen concentration of 99.9%.
[0068] The unit of oxygen permeability coefficient is 10 -14 cm 3 ·cm·cm -2 ·s -1 ·Pa -1 .
[0069] The lower the oxygen permeability coefficient, the higher the oxygen barrier property of the polymer.
[0070] The test data are shown in Table 2.
[0071] Table 2 Test data table of Examples 1-4 and Comparative Examples 1-4
[0072] Melt flow rate (MFR) g / 10min Oxygen permeability coefficient Example 1 15.4 4.879 Example 2 15.7 4.899 Example 3 16.0 4.904 Example 4 12.6 4.872 Comparative Example 1 75.5 4.885 Comparative Example 2 19.9 5.093 Comparative Example 3 23.8 4.267 Comparative Example 4 19.6 7.771
[0073] Referring to Example 1 and Comparative Example 1 and in combination with Table 2, it can be seen that, relative to Example 1, the melt mass flow rate of Comparative Example 1 is significantly improved, while the oxygen permeability coefficient of Comparative Example 1 is only slightly improved, which indicates that the addition of polymeric carbodiimide can effectively improve the hydrolysis resistance of the hydrolysis-resistant high-barrier biodegradable film.
[0074] The reason is that the reason that affects the hydrolysis of polyester is that water molecules attack the ester bonds in the polyester molecules and cause the polymer chain to break, and the terminal carboxyl group can accelerate the hydrolysis stability of the ester bond. Therefore, controlling the concentration of the terminal carboxyl group is one of the main means to improve the hydrolysis of polyester, and the carbodiimide group of the polymeric carbodiimide can react with the carboxyl group produced by hydrolysis, thereby effectively slowing down the continued occurrence of hydrolysis.
[0075] With reference to Example 1 and Comparative Example 2 and in combination with Table 2, it can be seen that, relative to Example 1, the melt mass flow rate of Comparative Example 2 is significantly improved, and the oxygen permeability coefficient of Comparative Example 2 is also significantly improved, which indicates that replacing 2,5-thiophenedicarboxylic acid with the same molar amount of dimethyl terephthalate will simultaneously reduce the hydrolysis resistance and gas barrier properties of the hydrolysis-resistant high-barrier biodegradable film.
[0076] The reason is that the molecular chain of aromatic dibasic acid contains thiophene ring, so it is difficult to flip. In addition, its hydrophilicity is poor, which leads to significant improvement in the gas barrier performance and hydrolysis resistance of the hydrolysis-resistant high-barrier biodegradable film.
[0077] Referring to Example 1 and Comparative Example 3 and in combination with Table 2, it can be seen that, relative to Example 1, the melt mass flow rate of Comparative Example 3 is significantly improved, while the oxygen permeability coefficient of Comparative Example 3 is significantly reduced. This shows that the addition of thiodiglycol can significantly improve the gas barrier properties of the hydrolysis-resistant high-barrier biodegradable film, but will also significantly reduce the hydrolysis resistance of the hydrolysis-resistant high-barrier biodegradable film.
[0078] The reason is that when thiodiglycol is introduced, sulfur will be connected to the molecular chain of the hydrolysis-resistant high-barrier biodegradable film as a heteroatom, thereby reducing the crystallinity of the hydrolysis-resistant high-barrier biodegradable film, thereby improving the gas barrier performance of the hydrolysis-resistant high-barrier biodegradable film. However, at the same time, sulfur atoms have good electronegativity and polarity, which promotes the hydrolysis-resistant high-barrier biodegradable film to obtain better hydrophilicity, and instead increases the hydrolysis rate of the hydrolysis-resistant high-barrier biodegradable film. Therefore, after comprehensive consideration, it is still chosen not to add thiodiglycol.
[0079] Referring to Comparative Examples 2 and 4 and in combination with Table 2, it can be seen that the melt mass flow rate of Comparative Example 4 is substantially unchanged compared with Comparative Example 2, while the oxygen permeability coefficient of Comparative Example 4 is significantly improved. This indicates that the addition of 2-ethyl-2-butyl-propylene glycol can effectively improve the gas barrier properties of the hydrolysis-resistant high-barrier biodegradable film.
[0080] The reason is that the vacancy steric hindrance of the side chain group in the 2-ethyl-2-butyl-propylene glycol monomer reduces the gas permeation, which significantly improves the gas barrier effect of the hydrolysis-resistant high-barrier biodegradable film.
[0081] Referring to Examples 1-3 and in combination with Table 2, it can be seen that, relative to Example 1, the melt mass flow rates of Examples 2-3 are significantly improved, and the oxygen permeability coefficients of Examples 2-3 are also significantly improved. This indicates that when the aromatic dibasic acid, aliphatic dibasic acid, aliphatic diol, 2-ethyl-2-butyl-propylene glycol and polymeric carbodiimide adopt the molar ratio of Example 1, the prepared hydrolysis-resistant high-barrier biodegradable film will have better gas barrier properties and hydrolysis resistance.
[0082] Referring to Example 1 and Example 4 and in combination with Table 2, it can be seen that, relative to Example 1, the oxygen permeability coefficient of Example 4 is substantially unchanged, while the melt mass flow rate of Example 4 is significantly reduced, which indicates that replacing 2,5-thiophenedicarboxylic acid with the same molar amount of dimethyl 2,5-thiophenedicarboxylate can further improve the hydrolysis resistance of the hydrolysis-resistant high-barrier biodegradable film.
[0083] The reason is that the aromatic dibasic acid can be 2,5-thiophene dicarboxylic acid or 2,5-thiophene dicarboxylic acid ester, but compared with 2,5-thiophene dicarboxylic acid, 2,5-thiophene dicarboxylic acid ester has no acid group, which effectively reduces the acid value and improves the hydrolysis resistance of the hydrolysis-resistant high barrier biodegradable film to a certain extent.
[0084] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A hydrolysis-resistant high-barrier biodegradable film, characterized in that: The invention is obtained by esterification and polycondensation of aromatic dibasic acid, aliphatic dibasic acid, aliphatic diol, 2-ethyl-2-butyl-propylene glycol and polymeric carbodiimide, and the molecular chain of the aromatic dibasic acid contains a thiophene ring.
2. The hydrolysis-resistant high-barrier biodegradable film according to claim 1, characterized in that: The aromatic dibasic acid is one of 2,5-thiophene dicarboxylic acid or 2,5-thiophene dicarboxylic acid esters.
3. The hydrolysis-resistant high-barrier biodegradable film according to claim 2, characterized in that: The aromatic dibasic acid is a 2,5-thiophene dicarboxylic acid ester, and the 2,5-thiophene dicarboxylic acid ester is one of 2,5-thiophene dicarboxylic acid dimethyl ester, 2,5-thiophene dicarboxylic acid diethyl ester, 2,5-thiophene dicarboxylic acid dipropyl ester and 2,5-thiophene dicarboxylic acid dibutyl ester.
4. The hydrolysis-resistant high-barrier biodegradable film according to claim 1, characterized in that: The aliphatic dibasic acid is one of oxalic acid, succinic acid, adipic acid, glutaric acid, 1,1-cyclohexanedicarboxylic acid, itaconic acid and maleic acid.
5. The hydrolysis-resistant high-barrier biodegradable film according to claim 1, characterized in that: The aliphatic diol is one of 1,2-ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,6-hexanediol, 1,4-cyclohexanediol and isosorbide.
6. The hydrolysis-resistant high-barrier biodegradable film according to claim 1, characterized in that: The polymeric carbodiimide is prepared from the following raw materials: toluene diisocyanate-80, methanol and 3-methyl-1-phenyl-2-phospholene-1-oxide.
7. The hydrolysis-resistant high-barrier biodegradable film according to claim 6, characterized in that: The preparation method of the polymeric carbodiimide is: First, under nitrogen, methanol is slowly added dropwise to toluene diisocyanate-80 for end-capping. The addition time is 0.5-1.5h, and the amount of methanol added is 30% of the amount of toluene diisocyanate-80. After the methanol is added dropwise, add 0.01-0.02% of the total amount of toluene diisocyanate-80 as a catalyst 3-methyl-1-phenyl-2-phospholene-1-oxide, raise the temperature to 100-140°C, and react for 2-4h; After the reaction is complete, the mixture is taken out and cooled to harden, then heated to 120-160°C and vacuum dried, and finally naturally cooled, fixed and crushed to obtain polymeric carbodiimide.
8. The hydrolysis-resistant high-barrier biodegradable film according to claim 1, characterized in that: The molar ratio of the aromatic dibasic acid, aliphatic dibasic acid, aliphatic diol, 2-ethyl-2-butyl-propylene glycol and polymeric carbodiimide is (0.45-0.5): (0.5-0.55): (0.6-1.6): (0.06-0.16): (0.1-0.2): (0.01-0.03).
9. A method for preparing a hydrolysis-resistant high-barrier biodegradable film according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. First, aliphatic diol, 2-ethyl-2-butyl-propylene glycol, aliphatic dibasic acid, aromatic dibasic acid and n-butyl titanate are mixed and subjected to esterification reaction at a temperature of 160-220° C. The amount of n-butyl titanate added is 10% of the amount of aliphatic diol added. The reaction is carried out for 2-3 hours to obtain an esterified product. S2. The esterification product is subjected to vacuum polycondensation reaction at a temperature of 220-240°C for a reaction time of 0.5-1.5h, and then 5% of the total mass of n-butyl titanate is added, and the vacuum polycondensation reaction is continued at 230-250°C for a reaction time of 2-4h, and then polymeric carbodiimide is added. After mixing evenly, extrusion cooling and stretching are performed to obtain a hydrolysis-resistant, high-barrier, biodegradable film with a thickness of 0.05-0.15mm.
Citation Information
Patent Citations
Heteroatom-containing high-barrier biodegradable copolyester and preparation method and application thereof
CN112375214A
Synthesis method and application of copolymerized polycarbodiimide
CN112920359A
High-crystallinity copolyester as well as preparation method and product thereof
CN115368545A